Detection of Acute Optic Neuritis using Contrast-Enhanced 3-Dimensional Cube T1-Weighted Imaging: A Preliminary Study - Yang, Renjie; Qu, Bing; Liu, Weiyin V.; Liu, Changsheng; Chen, Ting; Li, Liang; Zha, Yunfei (Combinatorial Chemistry & High Throughput Screening, 2023)
Objective; We aimed to assess whole-brain imaging with contrast-enhanced (CE) 3- dimensional (3D) Cube T1WI in improving the diagnostic accuracy of acute optic neuritis (ON) compared to conventional CE 2-dimensional (2D) T1WI. Methods: At a field strength of 3 T, CE 3D Cube T1-weighted and conventional CE 2D T1- weighted MR images were retrospectively analyzed for 32 patients (64 optic nerves) with clinically confirmed acute ON. The study cohort included 36 pathological nerves. Image assessments including the overall image quality, clarity of the optic nerve, and visual contrast enhancement were performed by two blinded neuroradiologists using a 4-point scale. The sensitivity, specificity, and accuracy of the conventional 2D T1WI and 3D Cube T1WI were calculated according to the clinical diagnosis. Results: The application of 3D Cube T1WI improved the overall image quality compared to 2D Ax T1WI and 2D Cor T1WI (P < 0.05). The clarity of the optic nerve and the visual contrast enhancement were higher for the 3D Cube T1WI compared to the 2D Ax T1WI and 2D Cor T1WI for at least one reader. The sensitivity, specificity, and accuracy were 89%, 86%, 88% for the 3D Cube T1WI respectively, and 75%, 79%, 77% for the conventional 2D T1WI respectively. The lesions detected by the conventional 2D T1WI were all detected by the 3D Cube T1WI. Conclusion: Our data show that whole-brain imaging with CE 3D Cube T1WI is a viable alternative for the detection of acute ON without sacrificing scanning efficiency.
Keywords: cube